Pengaruh Lama Penyimpanan pada Chiller terhadap Zat Gizi dan Karakteristik Sensoris Menu Hot Plate Choice A di PT. Aerofood ACS Denpasar - Wardani, Ni Putu Dewi Kusuma; Puspawati, Gusti Ayu Kadek Diah; Yusasrini, Ni Luh Ari (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 4 (2023): Jurnal ITEPADO - 10.24843/itepa.2023.v12.i04.p17, 2023)
Hot plate choice A is a type of main course produced by PT. Aerofood ACS Denpasar. The components of the Hot Plate Choice A menu are stored for 72 hours in a chiller at 5oC. Storage in cold (chilled) or frozen (frozen) conditions can affect the nutritional quality, decrease the quality, and sensory characteristics. This study aimed to determine the effect of storage time in the chiller on nutrients and sensory characteristics of the hot plate choice A menu and to determine the appropriate storage time for the hot plate choice A menu, which still has nutritional value and sensory characteristics suitable for consumption. The research method used a completely randomized design (CRD) with storage time treatments consisting of 8 levels, namely: (0 hours, 12 hours, 24 hours, 36 hours, 48 hours, 60 hours, 72 hours, and 84 hours). Each treatment was repeated 2 times to obtain 16 experimental units. The data obtained were analyzed using variance and if the treatment had a significant effect, then it was continued with the Duncan Multiple Range Test (DMRT). The results showed that storage time had a significant effect on moisture content, ash content, content fat, protein content, carbohydrate content, calorie content, and free fatty acid content Storage time in the chiller significantly affects moisture content, ash content, fat content, protein content, carbohydrate content, caloric value, and free fatty acid content, sensory preferences color, aroma, taste, texture, overall acceptability, colour, and textured scoring. The proper storage time to produce nutrients and sensory characteristics that are suitable for consumption in this study is at a storage time range of 0 hours to 24 hours with an average nutrient value at 24 hours storage, namely 56.069% water content, 1.101% ash content , protein content 38.999%, fat content 26.598%, free fatty acid content 0.020%, protein content 50.273%, caloric value 578.160 kcal, the color is liked slightly, color scoring with slightly, aroma is liked slightly, the texture is liked slightly, scoring texture with normal texture, the overall acceptance is liked slightly.